Muscle activation of the knee extensors following high intensity endurance exercise in cyclists - Bentley, D. J.; Smith, P. A.; Davie, A. J.; Zhou, S. (European Journal of Applied Physiology, 2000)
This study was conducted to assess the effects in trained cyclists of exhausting endurance cycle exercise (CE) on maximal isometric force production, surface electromyogram (EMG) and activation deficit (AD) of the knee extensors. Ten male subjects made four isometric maximal voluntary contractions (MVC) of the knee extensor muscles immediately prior (pre), 10 min after (post) and 6 h after completion of CE. The CE consisted of 30 min of exercise on a stationary cycle ergometer at an intensity corresponding to 80% of maximal oxygen uptake (VO2max) followed by four × 60-s periods at 120% of VO2max. Two MVC were performed with recording of surface EMG from the knee extensors, whilst an additional two MVC were completed with percutaneous electrical muscle stimulation (EMS; 25 pulses at 100 Hz with the maximal tolerable current) superimposed over the maximal voluntary contraction force (MVF) but without EMG (to avoid interference). The MVF, integrated EMG (iEMG), and AD [calculated as the difference between MVF and the electrically stimulated force (ESF) during the EMS contractions] were statistically analysed. The MVF was significantly reduced (P < 0.05) post and 6-h post compared to pre-CE level. The iEMG was significantly reduced (P < 0.05) post and 6 h post CE. The ESF was also reduced, whilst AD was significantly increased (P < 0.05) post and 6-h post CE compared to the pre CE. These results suggest that the level of exercise stress administered in this study was sufficient to impair the central and peripheral mechanisms of force generation in knee extensors for a period of 6-h. Athletes engaged in concurrent training (strength and endurance) should consider this effect in exercise programming.